A la tercera se gana: the validation of Benzingia (Orchidaceae: Zygopetalinae) - Romero González, Gustavo A. (2013)
When Benzingia was first proposed in 1989, the protologue included two species (Benzingia hirtzii sp. nov. and B. estradae comb. nov.), which required two separate Latin descriptions or diagnoses (generic and specific) for Benzingia and B. hirtzii. The author, however, provided only a descriptio generico-specifica. Therefore, the generic name, the new species, and the proposed combination were not validly published. An attempt to validate the genus and the two species was made by Dodson and Romero in 1995, but it also failed because it did not include separate Latin descriptions for the genus and the proposed type species. Seven species names referred to Benzingia in the meantime are also invalid. All the ten relevant names are here validated (the generic name, the new species, and eight new combinations).